1999
DOI: 10.1088/0022-3727/32/20/301
|View full text |Cite
|
Sign up to set email alerts
|

InAsSbP quantum dots grown by liquid phase epitaxy

Abstract: We report the growth of the first InAs-based quantum dots from the liquid phase using a novel rapid slider liquid phase epitaxial growth technique. Photoluminescence was observed at 4 K from these InAsSbP quantum dots encapsulated in GaAs and grown on a highly mismatched GaAs substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…InAsSbP quaternary alloy was successfully used for nucleation of quantum dots (QDs). In the first experiment to grow nanostructures with this quaternary composition, GaAs was used as a substrate (Krier, 1999). In that work the grown structure was characterized by photoluminescence (PL) measurements at 4 K temperature and the PL peak at 1.65 µm was observed.…”
Section: Introductionmentioning
confidence: 99%
“…InAsSbP quaternary alloy was successfully used for nucleation of quantum dots (QDs). In the first experiment to grow nanostructures with this quaternary composition, GaAs was used as a substrate (Krier, 1999). In that work the grown structure was characterized by photoluminescence (PL) measurements at 4 K temperature and the PL peak at 1.65 µm was observed.…”
Section: Introductionmentioning
confidence: 99%
“…These and other QD-based devices are expected to perform well at elevated temperatures due to their three-dimensional carrier confinement characteristics. [3][4][5] In these low dimensional structures, the movement of charge carriers is constrained by potential barriers. QDIPs are inherently sensitive to normal incidence radiation and also the dark current is much lower than that of QWIPs.…”
Section: Introductionmentioning
confidence: 99%
“…This fact together with a potentially lattice-matched growth on an InAs substrate makes InAsSbP unique in this material class. While InAsSbP quantum dots have been successfully grown previously, 3,7,8 only a few studies on quaternary cooperative QDs/leaves structures, so-called nano-camomiles, have been reported so far. 4,5 In particular, while charge carrier localization is expected in the central InAsSb-QD rather than in the surrounding InAsPleaves in these nano-camomiles, due to the conduction and valence band offsets of the dot, leaves and surrounding matrix material, long-ranged strain, and polarization potentials arising from the leaves are expected to induce a significant influence on the properties of the electrons and holes in the central dot.…”
Section: Introductionmentioning
confidence: 99%
“…This could be used as mixed compounds such as InAsSbP, a promising candidate because it can cover the 3-5 lm mid-infrared regions adjusting its alloy composition with three V elements only. It makes InAsSbP unique in this class and has been successfully grown on InAs substrates [17][18][19][20][21][22]. Actually, InAsSbP quantum dots have been successfully grown, while in contrast, only a few studies on quaternary QDs/nanopits nucleation have been reported so far [19,20].…”
Section: Introductionmentioning
confidence: 99%